EOBD USAGE IN LPG CONVERSIONS - Pogorevc, Primož; Tasič, Tadej; Biluš, Ignacijo (Journal of Energy Technology, 2024)
Aftermarket conversions of gasoline engines to also run on LPG are a way of reducing greenhouse gas emissions. The correct setup of the LPG system is necessary for optimal engine performance. If it is not set up correctly, the engine will not run properly, fuel consumption will increase, and the appearance of diagnostic trouble codes may activate the engine warning light. With European On-Board Diagnostics (EOBD), information from engine sensors throughout the car can be monitored and stored. Engine diagnostic trouble codes can also be read and cleared. This paper shows the usage of EODB for the optimal setup of aftermarket LPG systems. The analysis of the results obtained was made, and the LPG map was modified accordingly.